Re-considering the role of tumour length in oesophageal cancer staging: A prospective study from a tertiary care setting in South Asia - Qureshi, Sajida; Abbasi, Waqas Ahmad; Jalil, Hira Abdul; Waseem, Hira Fatima; Muhammad Saeed Quraishy (Journal of the Pakistan Medical Association, 2025)
Objective: To specifically evaluate the association between pre-neoadjuvant computed tomography-defined tumour length and clinical tumour-node-metastasis staging in oesophageal cancer patients. Method: The prospective study was conducted from August 2021 to August 2022 at the Dr Ruth K.M. Pfau Civil Hospital in Karachi, and comprised biopsy-confirmed oesophageal cancer inpatients. The tumour length was measured using pre-neoadjuvant computed tomography scans, and these were evaluated against clinical tumour-node-metastasis staging and other patient characteristics. Data was analysed using SPSS 26. Results: Of the 171 patients, 90(52.6%) were females and 81(47.4%) were males. The overall mean age was 47.46±14.12 years (range: 17-80 years). The tumour length determined by pre-neoadjuvant computed tomography scans as <5 cm, 5-10cm and >10cm showed significant correlations with tumour stage (p=0.006) and metastasis (p=0.011). Univariate analysis indicated that tumour stage 3 (p=0.020) and metastasis (p=0.005) were significantly associated with tumour length >10cm. Multivariate analysis confirmed that tumour stage 3 was significantly linked to tumour length >10cm (p=0.039). Conclusion: the tumour length determined by pre-neoadjuvant computed tomography scans in oesophageal cancer staging significantly correlated with clinical tumour-node-metastasis. Key Words: Oesophageal cancer, Neoplasm size, Cancer staging, Computed tomography, South Asia.